Hodgkin lymphoma: hypodense lesions in mediastinal masses - Damek, Adrian; Kurch, Lars; Franke, Friedrich Christian; Attarbaschi, Andishe; Beishuizen, Auke; Cepelova, Michaela; Ceppi, Francesco; Daw, Stephen; Dieckmann, Karin; Fernández-Teijeiro, Ana; Feuchtinger, Tobias; Flerlage, Jamie E; et al. (Scientific reports, 2024)
Hypodense volumes (HDV) in mediastinal masses can be visualized in a computed tomography scan in Hodgkin lymphoma. We analyzed staging CT scans of 1178 patients with mediastinal involvement from the EuroNet-PHL-C1 trial and explored correlations of HDV with patient characteristics, mediastinal tumor volume and progression-free survival. HDV occurred in 350 of 1178 patients (29.7%), typically in larger mediastinal volumes. There were different patterns in appearance with single lesions found in 243 patients (69.4%), multiple lesions in 107 patients (30.6%). Well delineated lesions were found in 248 cases (70.1%), diffuse lesions were seen in 102 cases (29.1%). Clinically, B symptoms occurred more often in patients with HDV (47.7% compared to 35.0% without HDV (p = 0.039)) and patients with HDV tended to be in higher risk groups. Inadequate overall early-18F-FDG-PET-response was strongly correlated with the occurrence of hypodense lesions (p < 0.001). Patients with total HDV > 40 ml (n = 80) had a 5 year PFS of 79.6% compared to 89.7% (p = 0.01) in patients with HDV < 40 ml or no HDV. This difference in PFS is not caused by treatment group alone. HDV is a common phenomenon in HL with mediastinal involvement.
Keywords: senioři; mediastinum; Positron-Emission Tomography; fluorodeoxyglukosa F18; Tomography, X-Ray Computed; mladiství; doba přežití bez progrese choroby; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Hodgkin Disease; nádory mediastina; Fluorodeoxyglucose F18; Mediastinal Neoplasms; Young Adult; ženské pohlaví; Humans; pozitronová emisní tomografie; Progression-Free Survival; lidé středního věku; Hodgkinova nemoc; Mediastinum; dospělí; počítačová rentgenová tomografie; Female; Aged; Adolescent; lidé; Male